On the h-Cobordism Category I. (19th December 2019) - Raptis, George; Steimle, Wolfgang
Abstract: We consider the topological category of $h$ -cobordisms between smooth manifolds with boundary and compare its homotopy type with the standard $h$ -cobordism space of a compact smooth manifold.